Model-driven Risk Analysis for the Design of Safe Collaborative Robotic Applications - Askarpour, Mehrnoosh; Lestingi, Livia; Buran, Federico; Rossi, Matteo; Vicentini, Federico (2020 IEEE International Conference on Human-Machine Systems (ICHMS), 2020)
In human-robot collaboration (HRC), humans and robots share the same workspace while executing hybrid tasks. Their close proximity imposes higher possibility of contacts that could potentially be dangerous. Hence, physical safety and risk analysis become of utmost importance during system design.In this paper, we propose a tool-supported interactive technique that facilitates the design of safe HRC systems for designers by performing iterative risk analysis and suggesting risk reduction measures (RRMs) to mitigate unsafe physical contacts.